Lords of the land : indigenous property rights and the jurisprudence of empire - Hickford, Mark. (Oxford : Oxford University Press, 2011)
Through focusing on the political history of New Zealand during its imperial settlement, this book offers a fresh assessment of the history of indigenous property rights. It shows how native title became a constitutional frame within which political authority was formed and contested at the heart of empire and the colonial peripheries.
7. `Tribunals Independent of a Prince', 1859-1862 -- Exploring the Dynamics and Consequences of `Occasional Association', Part II -- `Whatever may be the true theory of native tenure' -- of native title, mana, and seignorial rights -- Negotiations for the acquisition of the Pekapeka block in Waitara, 1859 and 1860 -- Warring memoranda -- setting the scene -- Indigenous orders, the conditionality of the introduced colonial constitution, and the three sticks of law, the divine being, and the mana of New Zealand in disunion -- Constitutional reflections -- living with indeterminacy and disagreement -- Communal or tribal rights, political autonomy, and rights of government as a parochial and trans-oceanic theme -- the political constitutionalism of native title, New Zealand, Algeria, and the law of nations -- `It seems agreed that native title is marvellously complex' -- Casting Waitara as a constitutional moment -- Martin's The Taranaki Question and a beginning to the warring of pamphlets -- `A country without law and a prince' -- the Treaty as an usher for rights-talk; individual and collective rights -- Who interprets? -- `Tribunals independent of the prince' and the meanings of the Treaty of Waitangi -- The Native Land Court, 1861-1862: a `Title Sifted Through' a statutory tribunal -- 8. Conclusions -- Constitutional Design and the Treaty of Waitangi: Balanced Constitutions, Native Title, and the Normativity of Political Constitutionalism.
Includes bibliographical references (p. [463]-499) and index.
Keywords: Geschichte 1830-1860.; Geschichte 1830-1860.; 1800-1899; Maori (New Zealand people) -- Land tenure; Maori (New Zealand people) -- Legal status, laws, etc; Land settlement -- Law and legislation -- New Zealand; Land settlement -- New Zealand -- History -- 19th century; Land settlement; Land settlement -- Law and legislation; Maori (New Zealand people) -- Land tenure; Maori (New Zealand people) -- Legal status, laws, etc; Grundeigentum; Imperialismus; Indigenes Volk; Rechtsprechung; Mana whenua; Ture; Mana whakairo hinengaro; 2; New Zealand; Neuseeland; History